2018
DOI: 10.1111/ele.12901
|View full text |Cite
|
Sign up to set email alerts
|

Thermal biology mediates responses of amphibians and reptiles to habitat modification

Abstract: Human activities often replace native forests with warmer, modified habitats that represent novel thermal environments for biodiversity. Reducing biodiversity loss hinges upon identifying which species are most sensitive to the environmental conditions that result from habitat modification. Drawing on case studies and a meta-analysis, we examined whether observed and modelled thermal traits, including heat tolerances, variation in body temperatures, and evaporative water loss, explained variation in sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
115
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 69 publications
(98 reference statements)
1
115
0
Order By: Relevance
“…This provides further evidence that the degree to which a species is thermally constrained correlates positively with forest dependence. Another possibility is that an alternative metric of thermal sensitivity, perhaps based on species' physiological responses to temperature extremes (Khaliq et al 2014, Frishkoff et al 2015, Nowakowski et al 2018, would provide a more robust test of the link with sensitivity to forest loss. 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides further evidence that the degree to which a species is thermally constrained correlates positively with forest dependence. Another possibility is that an alternative metric of thermal sensitivity, perhaps based on species' physiological responses to temperature extremes (Khaliq et al 2014, Frishkoff et al 2015, Nowakowski et al 2018, would provide a more robust test of the link with sensitivity to forest loss. 6).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, on average, tropical agricultural lands are 7.6°C warmer than tropical primary forest (Senior et al 2017). those with narrower thermal tolerances, hereafter 'thermal specialists') might be more sensitive to forest loss and degradation (Nowakowski et al 2018), especially to the replacement of forest with agriculture. Therefore, species adapted to highly seasonal environments (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Preferred temperature is significantly related to heat tolerance (Llewelyn, Macdonald, Hatcher, Moritz, & Phillips, ), so it is likely that species that perform well at high temperatures can also survive higher temperatures for longer periods of time. This is a beneficial trait for survival in human‐converted habitats, considering nonforested plots were on average 5.22 and 6.71°C hotter than forested plots on St. Eustatius and St. Martin, respectively, and recent studies have demonstrated that thermal tolerance largely explains reptile responses to human land use (Brusch, Taylor, & Whitfield, ; Frishkoff, Hadly, & Daily, ; Nowakowski et al., ). High sexual size dimorphism has previously been associated with low levels of intraspecific competition for food and resources (Latella, Poe, & Giermakowski, ), and larger headed reptiles are able to consume a wider range of prey sizes (Schoener & Gorman, ), suggesting that nonforested sites have a more variable prey community.…”
Section: Discussionmentioning
confidence: 99%
“…; Nowakowski et al . ). Evolutionary patterns in species’ ability to persist in the face of human‐induced environmental change have also emerged for certain taxa: across several systems birds that are evolutionarily distinct tend to be disproportionately lost from human‐modified agricultural (Frishkoff et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, a reliance on forests may predispose rapidly diversifying species to local extinction from land conversion, consistent with evidence that amphibian species within converted habitats are more distantly related than communities in natural habitats (Nowakowski et al . ). At the broader‐scale of global threat status, previous work indicates that rapidly diversifying amphibian genera have a high proportion of range‐restricted, threatened species (Greenberg & Mooers ), though at the species‐level evolutionary distinctiveness is not a strong predictor of threat status (Jetz & Pyron ).…”
Section: Introductionmentioning
confidence: 97%